Research Universities in Africa - Cloete, Nico (African Minds, 2018)
"From the early 2000s, a new discourse emerged, in Africa and the international donor community, that higher education was important for development in Africa. Within this 'zeitgeist' of converging interests, a range of agencies agreed that a different, collaborative approach to linking higher education to development was necessary. This led to the establishment of the Higher Education Research and Advocacy Network in Africa (Herana) to concentrate on research and advocacy about the possible role and contribution of universities to development in Africa. This book is the final publication to emerge from the Herana project. The project has also published more than 100 articles, chapters, reports, manuals and datasets, and many presentations have been delivered to share insights gained from the work done by Herana. Given its prolific dissemination, it seems reasonable to ask whether this fourth and final publication will offer the reader anything new. This book is certainly different from previous publications in several respects. First, it is the only book to include an analysis of eight African universities based on the full 15 years of empirical data collected by the project. Second, previous books and reports were published mid-project. This book has benefited from an extended gestation period allowing the authors and contributors to reflect on the project without the distractions associated with managing and participating in a large-scale project. For the first time, some of those who have been involved in Herana since its inception have had the opportunity to at least make an attempt to see part of the wood for the trees. Different does not necessarily mean new. An emphasis on the 'newness' of the data and perspectives presented in this book is important because it shows that it is more than a historical record of a donor-funded project. Rather, each chapter in this book brings, to a lesser or greater extent, something new to our understanding of universities, research and development in Africa."